TECHNICAL EDUCATION AND COMPUTING SUPPORT OF MATHEMATICS APPLICATIONS - VAGASKA, Alena (Trends in education, 2011)
The paper presents the possibilities of MS Excel and Matlab program equipment utilisation with mathematics applications to engineering subjects at technical universities.
Keywords: technical education; mathematics applications; MS Excel; Matlab.